Preliminary study of ODSee System : Understanding type of switches data format and viable online transfer mechanism / Nor'aini Ahmad - Ahmad, Nor'aini (2004)
This research is proposed with the objectives of proposing the online data collection of call data records generated by switches to replace the tape dump activity done by switch personnel. Currently, all the processing at the telephone switches and billing center is done manually and this resulted in highly inefficient process of tape handling which in turn delay production of bill and late customer billing. A few telephone switches will be selected for the study and the methods that will be using are face to face interview. Secondary data from the Internet, articles and also Telekom report will also be added to the findings. The system developed will help the network and billing group to manage call data transfer and billing processing more efficiently and effectively. Electronic data collection and pre-billing processing solutions was the methodology proposed in this research. The scope of my research are to study and analyze the protocol required in various type of switch namely Fujitsu, Alcatel and Nokia and the network protocol that interface the billing system to be implemented. This system is anticipated to significantly reduce data management's time, data and human errors and improved customer services on billing. It is also anticipated that over time, this system will also reduce maintenance cost for magnetic tape drive and also will improve TM cash flow.